ISLAMIC CHARACTER EDUCATION PATTERNS IN THE FAMILY ACCORDING TO HAMKA - Muhammad Rifi Harahap (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Islamic character education in the family plays an important role in shaping children's personalities based on Islamic values. Buya Hamka's thoughts on character education emphasize the importance of the family as the main foundation in instilling noble moral values ​​and faith. This study aims to identify the pattern of Islamic character education in the family according to Hamka's perspective, by referring to his works and thoughts, especially those related to ethics, morality, and Islamic character development. This study uses a qualitative method with a literature study approach, analyzing Hamka's works such as Tafsir Al-Azhar and the book Lembaga Budi. The results of the study show that Hamka emphasized three main components in Islamic character education: (1) parental exemplars in implementing Islamic values, (2) habituation of worship and noble morals in daily life, and (3) strengthening spirituality through instilling the values ​​of monotheism. In addition, Hamka also emphasized the importance of harmonious communication in the family to build an environment conducive to the formation of Islamic character. These findings contribute to the development of Islamic character education patterns that are relevant to the challenges of modern Muslim families.